Differences and Similarities in Rural Residents' Health and Cardiac Risk Factors - Florence M. Weierbach; Bernice Yates; Melody Hertzog; Bunny Pozehl (Rural Nurse Organization; Binghamton University, 2013)
Purpose: The current U.S. population exceeds three hundred million with approximately 20% living in non-urban rural areas. A higher percentage of rural residents have diagnosed heart disease and report poorer health compared to non-rural residents; however, it is not known whether risk factor modification for heart disease and health status differ based on degree of rurality. The purposes of this study were: 1) to compare differences in health status and cardiac risk factors between cardiac patients living in large and small/isolated rural areas, and 2) to compare the health status of rural cardiac patients with a national sample. Method: A secondary analysis using data from three separate studies was completed using a comparative descriptive design. The Cardiac Rehabilitation participant sample (n-191) included individuals 3 to 12 months post-cardiac event. The Arizona Heart Institute and Foundation Heart Test measured risk factors and the eight subscales of the Short-Form, Medical Outcomes study measured health status. Findings: No significant differences in health status were found; all participants rated their health moderately high. However, individuals in large rural areas reported significantly better general health than those in the normative sample. No differences in smoking, blood pressure, diabetes, or overweight/obese BMI were found between the two rural groups. Differences in exercise, and anger were present between the two groups. Significant differences were identified in waist circumference between the genders placing women at higher risk for heart disease. Conclusions: Identifying health status and cardiovascular risk factors of rural individuals informs interventions to be tested for rural residents. Key Words: Cardiac risk factors, Rural, Cardiac rehabilitation